Pengaruh Penggunaan Media Pembelajaran Berbasis Video Animasi Terhadap Hasil Belajar Dan Respon Siswa Kelas VII Dalam Proses Pembelajaran Matematika - Morrines Elfrida Sitompul; Septriana Manik; Abimanyu Pembayun; Rara Tri Ayu; Rosmaini (PT PUSTAKA CENDEKIA GROUP, 2024)
This research aims to determine student responses using animated video media at Putri Cahaya Medan Middle School. The methods used are observation, questionnaire and pretest methods. The subjects of this research were classes VII A and VII B. The indicators of student response studied were students listening to explanations of learning using media, students being active and responsive in learning, students daring to ask questions, and students daring to express opinions. Analysis of the questionnaire results shows that there is an increase in student responses to mathematics learning when using animated video-based learning media. Students felt happy with the learning atmosphere at 93.45%, students felt interested in the learning model at 9o.68%, and students felt it was a bit difficult to answer the learning outcomes test questions at 86.23%. This shows that animated visualization can help students understand mathematical concepts better